PERSEPSI CALON GURU SEKOLAH DASAR TERHADAP PELESTARIAN AKSARA LOKAL SASAMBO DI NTB - Widodo, Arif; Umar, Umar; Sutisna, Deni; Tahir, Muhammad (Jurnal Pendidikan dan Kebudayaan Missio, 2020)
Local script is one of the local wisdoms that must be preserved. Primary school education plays an important role in the preservation of local writing. This study aims to determine the perception of prospective elementary school teachers towards the preservation of local writing. the intended local writing is the Sasambo script in NTB. This research uses a combined method. Data collection using questionnaires and interviews. The results of the questionnaire were analyzed using descriptive statistics. Interview results were analyzed qualitatively. This study involved the University of Mataram PGSD students as respondents. The problems studied include: how is the motivation of prospective teachers in preserving local writing? What do prospective teachers do in preserving local writing? What are the difficulties experienced by prospective teachers in preserving local writing? The results showed that the motivation of prospective elementary school teachers in preserving local writing was still quite high. However, prospective teachers have difficulty in preserving local writing. Difficulties faced by prospective teachers include: local writing is rarely used, low community interest in learning, lack of teachers, lack of facilities and infrastructure, lack of literature, low awareness and low literacy. Efforts to preserve local writing by prospective elementary school teachers include: studying local writing, conducting training, and holding competitions. Local writing preservation programs in NTB need attention. The attention of prospective teachers, the government and the community can save local writing from extinction